Measuring the Effect of the Zero Lower Bound on Monetary Policy - Carlos Viana de Carvalho; Eric Hsu; Fernanda Nechio (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2016)
The Zero Lower Bound (ZLB) on interest rates is often regarded as an important constraint on monetary policy. To assess how the ZLB affected the Fed's ability to conduct policy, we estimate the effects of Fed communication on yields of different maturities in the pre-ZLB and ZLB periods. Before the ZLB period, communication affects both short- and long-dated yields. In contrast, during the ZLB period, the reaction of yields to communication is concentrated in longer-dated yields. Our findings support the view that the ZLB did not put such a critical constraint on monetary policy, as the Fed retained some ability to affect long-term yields through communication.
Keywords: E43; E52; E58; 330; communication; forward guidance; zero lower bound